2015
DOI: 10.4103/0255-0857.150908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis A virus (HAV) and Hepatitis E virus (HEV) in the patients presenting with acute viral hepatitis

Abstract: Though the prevalence of HAV is much higher than that of HEV, co-infection rate of 11.5% mandates the screening for HEV which will be of immense importance in pregnant women and improving levels of personal hygiene among higher socio-economic population. These data will be essential for planning of future vaccination strategies and for better sanitation programme in this part of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 6 publications
4
31
0
1
Order By: Relevance
“…It is supported by other studies conducted by various authors. [21][22][23][24] The overall incidence of both HAV and HEV was more in males (73.1% and 72.1%), and this finding is similar to that reported by Mittal 15 In literature, similar results were observed in other studies also. 13,18,[24][25][26][27] It is because of greater exposure of males in their professional and social activities.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…It is supported by other studies conducted by various authors. [21][22][23][24] The overall incidence of both HAV and HEV was more in males (73.1% and 72.1%), and this finding is similar to that reported by Mittal 15 In literature, similar results were observed in other studies also. 13,18,[24][25][26][27] It is because of greater exposure of males in their professional and social activities.…”
Section: Resultssupporting
confidence: 81%
“…14 In our study, among the two enterally transmitted viruses, the overall prevalence of HAV (15.4%) was more than HEV (13.9%). Singh et al 13 and Joon et al 15 reported the HAV seropositivity was more (32.1% and 19.31%) than that of HEV (7.19% and 10.54%). In contrast to our study, Kumar et al, 16 Nandi et al, 17 Antony and Celine 18 Manmohan et al, 19 and Mittal et al 20 reported higher prevalence of HEV (37.4%, 45.4%, 61.24%, 37.49%, and 14.9% respectively) as compared to HAV (14.6%, 33%, 31.54%, 32%, and 7.67%, respectively).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…HAV and HEV are waterborne viruses that usually cause acute hepatitis without progressing to chronic liver diseases (5, 6). According to the Global Burden of Disease study, 101.7 million cases of HAV and 28.4 million cases of HEV infection occurred worldwide in 2013 (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a China, Song et al (24) observed that BOD 5 and COD removal in wetlands was more efficient in spring and summer than in autumn and winter. The higher efficiency of sewage treatment in warm weather and the predominant prevalence of HAV during winter months (25) could justify the positive results of HAV presence in cold weather.…”
Section: Discussionmentioning
confidence: 99%